The margin of appreciation doctrine: a low‐level institutional view. (9th August 2015) - Tsarapatsanis, Dimitrios
Abstract : The paper argues that the margin of appreciation (MoA) doctrine of the European Court of Human Rights (ECtHR, or Court), should be understood as, inter alia, an underenforcement doctrine, according to which Convention rights should not be applied to their full conceptual limits. Underenforcement is justified by institutional considerations relating to the Court's role and competence. Although institutional considerations have been theorised normatively, the paper claims that 'low‐level' empirical inquiry into the comparative institutional competence of different decision makers across the Council of Europe is critical in explaining MoA. Such comparative empirical analysis ties shared institutional responsibility and subsidiarity with certain traits of decision makers when determining Convention rights. In this context, the paper briefly compares the decision making abilities of different institutions. It concludes by stressing that under certain circumstances the Court can be worse placed than national authorities to decide on violations of Convention rights. This is corroborated by the Court's case‐law concerning Convention rights impinging on the economic and social policies of States Parties.